Linking resources to career satisfaction through work–family enrichment. Issue 11 (10th September 2019) - Rastogi, Mansi; Karatepe, Osman M.; Mehmetoglu, Mehmet
ABSTRACT: Using the work–family enrichment (WFE) model and social exchange theory as the theoretical underpinnings, our study investigates WFE as a mediator of the effects of material resources (i.e. salary, job security) as well as psychological resources (i.e. self-esteem) on career satisfaction. Our study gathered data from frontline employees (FLEs) in small- and medium-sized hotels in Delhi, the capital city of India, and gauged the aforementioned relationships through partial least squares structural equation modelling. The results suggest that FLEs' satisfaction with salary and job security needs fosters WFE that in turn gives rise to satisfaction with their career in the organisation. The results also suggest that FLEs' satisfaction with esteem needs stimulates WFE that in turn engenders career satisfaction. We discuss theoretical and practical implications of the empirical findings in the paper.